Sperm Storage Costs Determine Survival and Immunocompetence in Newly Mated Queens of the Leaf-Cutting Ant Atta colombica - Baer-Imhoof, Barbara; den Boer, Susanne P. A.; Boomsma, Jacobus J.; Baer, Boris (Frontiers in Ecology and Evolution, 2022)
In the leafcutter ant Atta colombica, queens receive ejaculates from multiple males during one single mating event early in their lives and never mate again once they have started to lay eggs. A queen's fertility and fitness therefore depend on maximizing the number of sperm cells she can store and maintain inside her spermatheca. Previous studies implied significant physiological mating costs, either originating from energetic investments maximizing sperm survival, or from resolving sexual conflicts to terminate male-driven incapacitation of rival sperm via serine proteases found in seminal fluid. Here we conducted an artificial insemination experiment, which allowed us to distinguish between the effects of sperm and seminal fluid within the queen’s sexual tract on her survival and immunocompetence. We found significantly higher mortality in queens that we had inseminated with sperm, independently of whether seminal fluid was present or not. Additionally, heavier queens that had received sperm had a higher probability of survival compared to lightweight queens, but immunocompetence decreased disproportionally for queens that had lost weight during the experiment. These findings indicate that queens pay significant physiological costs for maintaining and storing sperm shortly after mating. On the other hand, the presence of seminal fluid within the queens' sexual tract neither affected their survival nor their immunocompetence. This suggests that the energetic costs that queens incur shortly after mating are primarily due to investments in sperm maintenance and not to efforts to terminate conflicts between competing ejaculates. This outcome is consistent with the idea that sexually selected traits in social insects with permanent castes can evolve only when they do not affect survival or life-time fitness of queens in any significant way.